2017
DOI: 10.1021/acs.jpcc.7b04657
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Pressure-Induced Structural Behavior of CuCr2O4 and CuCr2Se4 Spinels

Abstract: We have conducted high-pressure measurements on the CuCr 2 O 4 and CuCr 2 Se 4 spinels to unravel the structural systematics of these materials under compression. Our studies have revealed diverse structural behavior in these two compounds. In particular, CuCr 2 O 4 retains its ambient-pressure I4 1 /amd structure up to 50 GPa. Close inspection of the lattice and interatomic parameters reveals a compressibility change near 23 GPa, which is accompanied by an expansion of the apical Cr−O bond distances. We specu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…The errors in the fitting results come from the fitting process without including the propagation of uncertainties from pressure and volume. The bulk modulus of the cubic phase of this lacunar spinel compound is different from other conventional spinels, such as ZnGa 2 O 4 , ZnCr 2 Se 4 , CoCr 2 O 4 , CuCr 2 O 4 , ZnCr 2 S 4 , MnCr 2 O 4 , NiCr 2 O 4 , CdCr 2 Se 4 , and so on. The discrepancies are predominantly caused by the different crystal structures, F 4̅3 m versus Fd 3̅ m , in these two systems.…”
Section: Results and Discussionmentioning
confidence: 74%
“…The errors in the fitting results come from the fitting process without including the propagation of uncertainties from pressure and volume. The bulk modulus of the cubic phase of this lacunar spinel compound is different from other conventional spinels, such as ZnGa 2 O 4 , ZnCr 2 Se 4 , CoCr 2 O 4 , CuCr 2 O 4 , ZnCr 2 S 4 , MnCr 2 O 4 , NiCr 2 O 4 , CdCr 2 Se 4 , and so on. The discrepancies are predominantly caused by the different crystal structures, F 4̅3 m versus Fd 3̅ m , in these two systems.…”
Section: Results and Discussionmentioning
confidence: 74%
“…We can immediately observe a linear dependence of the two parameters, with the exception of CuCr 2 O 4 which does not show any transition up to 50 GPa, whereas the P Tr = 25 GPa in this case indicates an isostructural transition, most likely resulting from a pressureinduced orbital reorientation 24 . We note also that the calculated magnetic exchange interactions of CuCr 2 O 4 are much larger compared to the rest of the spinels ( Table S8 in the Supplement 46 ), possibly accounting for the absence of any structural transition up to 50 GPa 24 . On the other hand, CoCr 2 O 4 undergoes a structural distortion at about 16 GPa, attributed to magnetic frustration 45 .…”
Section: Pressure-induced Structural Transition and Magnetic Exchamentioning
confidence: 69%
“…In particular, we have shown that the ratio of the next-nearest neighbor (K nnn ) over the nearest neighbor (J nn ) magnetic interactions is proportional to the structural transition pressure (P Tr ) from the starting cubic Fd3 m phase towards a tetragonal modification 21,22 . Notable exceptions from this trend are ZnCr 2 Se 4 23 and CuCr 2 Se 4 24 , as their high-pressure behavior appears to be dictated by the similar ionic radii of tetrahedrally coordinated Zn 2+ and Cu 2+ with the octahedrally coordinated Cr 3+ , and the higher covalency of the larger-sized Se anions [for a more detailed discussion see Ref. 24 ].…”
Section: Fig 1 the Crystal Structure Of The A 2+ Cr 3+mentioning
confidence: 99%
See 1 more Smart Citation
“…Copper chromite composite oxide is a versatile catalyst and has been employed as a catalyst for chemical reactions such as hydrogenation, dehydrogenation, oxidation, alkylation, etc. Accordingly, it finds a wide range of commercial applications . Recently, we have reported the photocatalytic property of CuCr 2 O 4 nanoparticles .…”
Section: Introductionmentioning
confidence: 99%